Analysis of The Entrepreneurial Intention’s Emergence at Business and non-Business Students in Indonesia - Astuty, Eriana; Yustian, Okky Rizkia (FKIP Universitas Lampung, 2021)
Analysis of The Entrepreneurial Intention’s Emergence at Business and non Business Students in Indonesia. Objective: This study confirm empirically the student entrepreneurial intentions (SEI) related to the study program, family background, students’ business experience; and describing the reflection of the SEI at several universities in Indonesia. Method: A survey-type quantitative approach, using descriptive, contingency, and CFA analysis. Findings: The Study programs have a relationship with the emergence of SEI. In addition, the family background in doing business and the student’s business experience did not show a relationship with SEI in business students, but against non-business students. Conclusion: Not only business study programs capable of arousing SEI, but non-business study programs can also trigger SEI, even though non-business study programs do not provide entrepreneurship learning as much as the business study program curriculum. This finding is interesting to discuss because it can explore what kind of business or non-business study programs can actually strengthen the SEI.Keywords: entrepreneurial intention, family background, business experience, study program, curriculum DOI: http://dx.doi.org/10.23960/jpp.v11.i1.202101